Assessment of fertilizing potential in crossbred breeding bulls by some current diagnostic approach in vitro* - DAS, H N; VERMA, R P; ANSARI, M R; MAJUMDAR, A C (The Indian Journal of Animal Sciences, 2012)
Semen samples collected from best selected breeding bulls of 2 different triple crossbreds were subjected to be tested by BCMPT, HOST and ZHPT after being evaluated routinely and the same samples were confirmed in field artificial insemination trials. Majority of the tests like individual motility, normal percentage, cold shock resistance and MBRT showed a significant positive correlation with fertility. In BCMPT, no statistical difference was observed with diluted semen, but observed significantly (P<0.05) with the neat semen which also exhibited a nonsignificant negative correlation with field AI trials. In HOST, the "g" type (total tail swollen) per cent ’of sperms revealed a significant difference (P<0.01) among the 4 bulls and showed a highly significant positive correlation with field fertility trials. In ZHPT, a significant (P<0.05) variation was observed among the bulls for FP and FI, but these 2 values indicated a nonsignificant negative correlation with field fertility trials. BCMPT, HOST and ZHPT can effectively be used in combination with conventional techniques in vitro to select a sire in crossbred bovine.